Current sensor fault-tolerant control based on modified Luenberger observers for safety-critical vector-controlled induction motor drives - Adamczyk, Michal; Orłowska-Kowalska, Teresa (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Vector-controlled drives require stator current information for use in current feedback and/or state variable estimators. That is why the detection and compensation of possible current sensor (CS) damage is so important. This article focuses on CS fault-tolerant control (FTC) in induction motor (IM) drive systems. In contrast to solutions known from the literature, two modified Luenberger observers (MLO) were applied, allowing for high-quality estimation of currents used in the detector and fault compensator. In a simple implementation of a detection algorithm based on residuals, an adaptive threshold coefficient was employed, enabling effective detection of various types of faults, regardless of whether the second CS was faulty or intact. The presented solution was evaluated during both motor and regenerative operation, with faults occurring in transient states, unlike solutions known in the literature.